2009
DOI: 10.1375/acri.42.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Intersections Between In-Court Procedures and the Production of Guilty Pleas

Abstract: In Australia (as elsewhere) most criminal defendants plead guilty and do not contest the charges at trial. Our research suggests that guilty pleas can result from an intersectional process, in which in-court events interact with out-of-court activities and discussions. This article draws on an observational study of criminal matters in Australian lower courts. It examines the early stages of in-court proceedings, in particular the ways in which the judicial officer's — here the magistrate — decisions about adj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…While this may hinder their ability to ensure guilty pleas are appropriately entered, the findings from this study also suggest that it may encourage judges to influence a defendant’s decision to plead guilty. Previous Australian research has found that magistrates used a variety of strategies to encourage guilty pleas that maintained an image of judicial neutrality (Roach Anleu & Mack, 2009). Similar findings were observed here, where judges influenced the decision to plead guilty by commenting on the strength of the case, encouraging the defendant to change their plea of not guilty during a court hearing, or by suggesting the defendant will avoid being held in pretrial detention.…”
Section: Discussionmentioning
confidence: 99%
“…While this may hinder their ability to ensure guilty pleas are appropriately entered, the findings from this study also suggest that it may encourage judges to influence a defendant’s decision to plead guilty. Previous Australian research has found that magistrates used a variety of strategies to encourage guilty pleas that maintained an image of judicial neutrality (Roach Anleu & Mack, 2009). Similar findings were observed here, where judges influenced the decision to plead guilty by commenting on the strength of the case, encouraging the defendant to change their plea of not guilty during a court hearing, or by suggesting the defendant will avoid being held in pretrial detention.…”
Section: Discussionmentioning
confidence: 99%
“…23-29;Natapoff, 2018). Finally, some of the most critical yet understudied legal questions involving defendant decision-making require grueling observational and interview research (Anleu & Mack, 2009;Clair, 2020;Smith & Maddan, 2011;van Cleve, 2016). Legal methodology and design matters further complicate studying these research gaps to understand rights assertion (Smith, 2019(Smith, , 2023.…”
Section: Introductionmentioning
confidence: 99%